In-situ monitoring by Raman spectroscopy of the thermal doping of graphene and MoS2 in O2-controlled atmosphere - Piazza, Aurora; Giannazzo, Filippo; Buscarino, Gianpiero; Fisichella, Gabriele; Magna, Antonino La; Roccaforte, Fabrizio; Cannas, Marco; Gelardi, Franco Mario; Agnello, Simonpietro (Beilstein Journal of Nanotechnology, 2017)
The effects of temperature and atmosphere (air and O2) on the doping of monolayers of graphene (Gr) on SiO2 and Si substrates, and on the doping of MoS2 multilayer flakes transferred on the same substrates have been investigated. The investigations were carried out by in situ micro-Raman spectroscopy during thermal treatments up to 430 °C, and by atomic force microscopy (AFM). The spectral positions of the G and 2D Raman bands of Gr undergo only minor changes during treatment, while their amplitude and full width at half maximum (FWHM) vary as a function of the temperature and the used atmosphere. The thermal treatments in oxygen atmosphere show, in addition to a thermal effect, an effect attributable to a p-type doping through oxygen. The thermal broadening of the line shape, found during thermal treatments by in situ Raman measurements, can be related to thermal phonon effects. The absence of a band shift results from the balance between a red shift due to thermal effects and a blue shift induced by doping. This shows the potential of in situ measurements to follow the doping kinetics. The treatment of MoS2 in O2 has evidenced a progressive erosion of the flakes without relevant spectral changes in their central zone during in situ measurements. The formation of MoO3 on the edges of the flakes is observed indicative of the oxygen-activated transformation.
Keywords: two-dimensional (2D) materials; graphene; MoS2; Raman spectroscopy; thermal doping

(untitled) - Geim, A. K.; Grigorieva, I. V. (Nature, 2013)

(untitled) - Nair, R. R.; Blake, P.; Grigorenko, A. N.; Novoselov, K. S.; Booth, T. J.; Stauber, T.; Peres, N. M. R.; Geim, A. K. (Science, 2008)

(untitled) - Bao, Q.; Zhang, H.; Wang, Y.; Ni, Z.; Yan, Y.; Shen, Z. X.; Loh, K. P.; Tang, D. Y. (Adv. Funct. Mater., 2009)

(untitled) - Xing, G.; Guo, H.; Zhang, X.; Sum, T. C.; Huan, C. H. A. (Opt. Express, 2010)

(untitled) - Bae, S.; Kim, H.; Lee, Y.; Xu, X.; Park, J.-S.; Zheng, Y.; Balakrishnan, J.; Lei, T.; Kim, H. R.; Song, Y., II; Kim, Y.-J.; Kim, K. S.; et al. (Nat. Nanotechnol., 2010)

(untitled) - Casaluci, S.; Gemmi, M.; Pellegrini, V.; Di Carlo, A.; Bonaccorso, F. (Nanoscale, 2016)

(untitled) - Berger, C.; Song, Z.; Li, X.; Wu, X.; Brown, N.; Naud, C.; Mayou, D.; Li, T.; Hass, J.; Marchenkov, A. N.; Conrad, E. H.; First, P. N.; et al. (Science, 2006)

(untitled) - Sonde, S.; Giannazzo, F.; Vecchio, C.; Yakimova, R.; Rimini, E.; Raineri, V. (Appl. Phys. Lett., 2010)

(untitled) - Reina, A.; Jia, X.; Ho, J.; Nezich, D.; Son, H.; Bulovic, V.; Dresselhaus, M. S.; Kong, J. (Nano Lett., 2009)

(untitled) - Li, X.; Cai, W.; An, J.; Kim, S.; Nah, J.; Yang, D.; Piner, R.; Velamakanni, A.; Jung, I.; Tutuc, E.; Banerjee, S. K.; Colombo, L.; et al. (Science, 2009)

(untitled) - Fisichella, G.; Di Franco, S.; Roccaforte, F.; Ravesi, S.; Giannazzo, F. (Appl. Phys. Lett., 2014)

(untitled) - Pirkle, A.; Chan, J.; Venugopal, A.; Hinojos, D.; Magnuson, C. W.; McDonnell, S.; Colombo, L.; Vogel, E. M.; Ru-off, R. S.; Wallace, R. M. (Appl. Phys. Lett., 2011)

(untitled) - Liu, H.; Liu, Y.; Zhu, D. (J. Mater. Chem., 2011)

(untitled) - Ryu, S.; Liu, L.; Berciaud, S.; Yu, Y.-J.; Liu, H.; Kim, P.; Flynn, G. W.; Brus, L. E. (Nano Lett., 2010)

(untitled) - Yamada, Y.; Murota, K.; Fujita, R.; Kim, J.; Watanabe, A.; Nakamura, M.; Sato, S.; Hata, K.; Ercius, P.; Ciston, J.; Song, C. Y.; Kim, K.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Mehmood, F.; Pachter, R.; Lu, W.; Boeckl, J. J. (J. Phys. Chem. C, 2013)

(untitled) - Liu, L.; Ryu, S.; Tomasik, M. R.; Stolyarova, E.; Jung, N.; Hybertsen, M. S.; Steigerwald, M. L.; Brus, L. E.; Flynn, G. W. (Nano Lett., 2008)

(untitled) - Das, A.; Pisana, S.; Chakraborty, B.; Piscanec, S.; Saha, S. K.; Waghmare, U. V.; Novoselov, K. S.; Krishnamurthy, H. R.; Geim, A. K.; Ferrari, A. C.; Sood, A. K. (Nat. Nanotechnol., 2008)

(untitled) - Piazza, A.; Giannazzo, F.; Buscarino, G.; Fisichella, G.; La Magna, A.; Roccaforte, F.; Cannas, M.; Gelardi, F. M.; Agnello, S. (J. Phys. Chem. C, 2015)

(untitled) - Piazza, A.; Giannazzo, F.; Buscarino, G.; Fisichella, G.; La Magna, A.; Roccaforte, F.; Cannas, M.; Gelardi, F. M.; Agnello, S. (Phys. Status Solidi A, 2016)

(untitled) - Piazza, A.; Giannazzo, F.; Buscarino, G.; Fisichella, G.; La Magna, A.; Roccaforte, F.; Cannas, M.; Gelardi, F. M.; Pignataro, B.; Scopelliti, M.; Agnello, S. (Carbon, 2016)

(untitled) - Matte, H. S. S. R.; Gomathi, A.; Manna, A. K.; Late, D. J.; Datta, R.; Pati, S. K.; Rao, C. N. R. (Angew. Chem., 2010)

(untitled) - Radisavljevic, B.; Radenovic, A.; Brivio, J.; Giacometti, V.; Kis, A. (Nat. Nanotechnol., 2011)

(untitled) - Guo, Y.; Wei, X.; Shu, J.; Liu, B.; Yin, J.; Guan, C.; Han, Y.; Gao, S.; Chen, Q. (Appl. Phys. Lett., 2015)

(untitled) - Yamamoto, M.; Einstein, T. L.; Fuhrer, M. S.; Cullen, W. G. (J. Phys. Chem. C, 2013)

(untitled) - Zhou, H.; Yu, F.; Liu, Y.; Zou, X.; Cong, C.; Qiu, C.; Yu, T.; Yan, Z.; Shen, X.; Sun, L.; Yakobson, B. I.; Tour, J. M. (Nano Res., 2013)

(untitled) - Chakraborty, B.; Bera, A.; Muthu, D. V. S.; Bhowmick, S.; Waghmare, U. V.; Sood, A. K. (Phys. Rev. B, 2012)

(untitled) - Islam, M. R.; Kang, N.; Bhanu, U.; Paudel, H. P.; Erementchouk, M.; Tetard, L.; Leuenberger, M. N.; Khondaker, S. I. (Nanoscale, 2014)

(untitled) - Ferrari, A. C.; Meyer, J. C.; Scardaci, V.; Casiraghi, C.; Lazzeri, M.; Mauri, F.; Piscanec, S.; Jiang, D.; Novoselov, K. S.; Roth, S.; Geim, A. K. (Phys. Rev. Lett., 2006)

(untitled) - Verhagen, T. G. A.; Drogowska, K.; Kalbac, M.; Vejpravova, J. (Phys. Rev. B, 2015)

(untitled) - Tian, S.; Yang, Y.; Liu, Z.; Wang, C.; Pan, R.; Gu, C.; Li, J. (Carbon, 2016)

(untitled) - Liu, Y.; Tan, C.; Chou, H.; Nayak, A.; Wu, D.; Ghosh, R.; Chang, H.-Y.; Hao, Y.; Wang, X.; Kim, J.-S.; Piner, R.; Ruoff, R. S.; et al. (Nano Lett., 2015)